(untitled) (Pravaha, 2024)
Financial literacy is essential for enabling individuals to make sound financial decisions, manage their resources wisely, and secure long-term financial well-being. In the context of entrepreneurship, financial literacy, combined with saving behavior, is a key driver in shaping entrepreneurial intention by providing individuals with the knowledge and discipline necessary to confidently start and sustain business ventures. This study explores the impact of financial literacy on entrepreneurial intention among business students in Nepal, with a special emphasis on the mediating role of saving behavior. To achieve the research objectives, primary data were gathered through a structured questionnaire, employing a convenience sampling technique for distribution. 411 undergraduate and graduate business students from universities in Nepal is take as the sample of the study. The structural relationships in the proposed model were assessed using Smart PLS 4.0. The results indicate that financial literacy has a significant positive impact on entrepreneurial intentions, with this effect being amplified by the presence of saving behavior. Financial literacy fosters entrepreneurial intentions by providing individuals with critical skills for making informed decisions and managing finances effectively. It enables them to plan, budget, and utilize resources wisely, which is crucial for starting and sustaining a business. Additionally, sound saving behavior provides the necessary capital for entrepreneurial ventures, especially in a context where formal funding options may be limited. Overall, financial literacy and disciplined saving behavior significantly boost the likelihood of successful entrepreneurship which contributes to economic growth in Nepal.